Dye-sensitized solar cells - Kalyanasundaram, K. (CRC Press, 2010)
"The dye-sensitized solar cell (DSC) is a photovoltaic converter that mimics natural photosynthesis. Like green plants and algae it uses a molecular absorber, the dye, to harvest sunlight and generate electric charges. Dye-sensitized solar cells are poised to replace existing technologies in «low density» solar-energy applications, especially in contexts where mechanical robustness and light weight is required. This book offers the first comprehensive look at this promising technology and aims to provide a graduate level text that brings together the fundamentals of DSC from three perspectives (materials, performance, and mechanistic aspects), as well as to serve as an advanced monograph that summarizes the key advances and lists the technical challenges remaining to be solved."--BOOK JACKET.